Urgensi Pendidikan Islam Untuk Pembangunan Manusia Di Era Millenial - Mukaffan Mukaffan; Ali Hasan Siswanto (Qolamuna : Jurnal Studi Islam, 2019)
This research is library research with qualitative-analytical descriptive approach. To analyses and process data, this research used by content analysis method, is analyses a content and meaning exist in text. Some conclusion in this research, first, history grow and expanding of Islamic education in this millennial era is very massive as an expression of human freedom to serve and improve its humanity. Second, Educational dynamics of Islam in millennial era provided knowledge in terms of quantity and quality; third, the emergence of Islamic education to answer the needs of a changing era. At least there are two factors underlying Islamic education in the millennial era. First, internal factors, the goodness of teaching and also human resource needs that required development in all fields. Second, external factors such as modernization and globalization. Keywords : Islamic education, millennial, humans